Early adversity and adult delinquency: the mediational role of mental health in youth offenders - Basto-Pereira, Miguel (2019)
This research explores the mediational role of mental health in the relationship between early adverse experiences and current self-reported delinquency in young adults with past juvenile justice involvement. Seventy-five young adults with official records of juvenile delinquency in 2010/2011 filled out our protocol in 2014/2015 including the Adverse Childhood Experiences (ACE) questionnaire, the Brief Symptom Inventory, and the D-CRIM questionnaire (evaluating delinquency). The global level of adverse experiences during childhood and adolescence was related to mental health problems and self-reported delinquency in young adulthood, while psychopathological symptoms were also related to current self-reported delinquency. The mental health indicator partially mediated the link between early adversity and current self-reported offending in individuals with past juvenile justice involvement. Our results are in line with previous psychological and neurobiological approaches and highlight the importance of mental health services in youth offender rehabilitation. Future directions for research are provided.